Pathogenic POGZ mutation causes impaired cortical development and reversible autism-like phenotypes - Kensuke Matsumura (Nature Portfolio, 2020)
De novo mutations significantly contribute to autism spectrum disorders (ASD). Here, the authors demonstrate that ASD-associated de novo mutations in the POGZ gene, one of a high-confidence ASD gene, lead to ASD-related impaired neuronal development and disrupted mature cortical network function.